MgO/Fe₂O₃ ratio mineralization-responsive intervals and their constraints on Cr-Ni-Co mineralization: From regional geochemical mapping to large-scale anomaly focusing and targeting - Zhao An; Zhenhua Zheng; Tao Wang; Qingyun Wang; Li He; Changwei Qi; Mingfu Zhao; Yulong Li; Youning Wei; Dong Zhang; Xiaojun Dong; Yong Wang (Journal of Geochemical Exploration, 2026)

Recent advances in spore-killing technologies: A comprehensive review on killing effect, mechanism and application in food matrices - Chenghao Li; Jiahao Ren; Muhammad Adil; Yiting Fan; Youning Zou; Xinglong Xiao (Food Microbiology, 2026)

Stochastic optimization for sustainable closed-loop electric vehicle battery supply chain networks - Haodong Li; Wenzhu Liao; Youning Qian (Environment, Development and Sustainability, 2026)

Migration and enrichment mechanisms of selenium, zinc, and iodine in the soil–plant–animal continuum of Yushu, Qinghai–Tibet plateau: insights from environmental geochemical factors - Zhao An; Siqi Han; Tao Wang; Haikui Tong; Li He; Changwei Qi; Qinyu Liu; Sheng Xue; Youning Wei; Yulong Li; Xiaojun Dong (Environmental Monitoring and Assessment, 2026)

Thermoexergetic analysis and response optimisation of selective exhaust gas recirculation with solvent-based CO2 capture in a natural gas-fired combined cycle power plant - Youning Tang; Cheng Tung Chong; Jo-Han Ng; Laura Herraiz; Jia Li; Hwai Chyuan Ong; Su Shiung Lam; Meisam Tabatabaei; William Woei Fong Chong (Clean Technologies and Environmental Policy, 2024)

Full-length transcriptomics study of Ustiloxins-induced hepatocyte injury - Guomei Zhang; Xuming Zhou; Shanshan Liu; Youning Ma; Han Li; Yingchun Du; Zhaoyun Cao; Lihua Sun (Toxicon, 2024)

Transcriptomic Signatures of Pearl Oyster Pinctada Maxima in Response to Acute Salinity Stress - Haijun Wei; Mingqiang Chen; Zhenghua Deng; Jing Sun; Jingru Yang; Wang Zhao; Youning Li; Zhenhua Ma; Yu Wang; Gang Yu (Frontiers in Marine Science, 2022)
Acute salinity stress can impact many physiological processes of marine shellfish. The responses of Pinctada maxima to salinity stress, especially the osmotic pressure regulation and immune response, are of great significance to health. To investigate the molecular changes in response to acute salinity stress, the pearl oysters were transferred from 30 ppt (C) to 40 ppt (HS) and 20 ppt (LS) for 12 h, and the transcriptome analysis was conducted on the gills. Compared to the control, there were 6613 (3253 up-regulated and 3360 down-regulated) differentially expressed genes (DEGs), 4395 (2180 up-regulated and 2215 down-regulated) DEGs observed in HS and LS, respectively. The related molecular biological processes and potential functions were explored from enrichment analysis. A total of 332 KEGG pathways (including 1514 genes) and 308 KEGG pathways (including 731 genes) were enriched in C vs. HS and C vs. LS, respectively. In addition, there are 1559 DEGs shared by C vs. HS group and C vs. LS group, and the results of the KEGG function annotation showed that 7 DEGs were involved in membrane transport, and 34 DEGs were involved in the immune system. The correlation network for expression of genes shows that the expression of 3 genes was significantly correlated with each other in membrane transport, and there were significant correlations between the expression of 27 genes in immune response. The results of this study will be of great value in understanding the molecular basis of salinity stress adaptation in the pearl oyster P. maxima .

Use of Monte Carlo simulation to evaluate the efficacy of tigecycline and minocycline for the treatment of pneumonia due to carbapenemase-producing Klebsiella pneumoniae - Wentao Ni; Guobao Li; Jin Zhao; Junchang Cui; Rui Wang; Zhancheng Gao; Youning Liu (Infectious Diseases, 2018)

H2O2 regulates root system architecture by modulating the polar transport and redistribution of auxin - Chao Su; Liu Liu; Haipei Liu; Brett J. Ferguson; Yanmin Zou; Yankun Zhao; Tao Wang; Youning Wang; Xia Li (Journal of Plant Biology, 2016)

Effects of prey color, wall color and water color on food ingestion of larval orange-spotted grouper Epinephelus coioides (Hamilton, 1822) - Jiasong Zhang; Huayang Guo; Zhenhua Ma; Shigui Jiang; Kaichang Wu; Youning Li; Jian G. Qin (Aquaculture International, 2015)

GmmiR156b overexpression delays flowering time in soybean - Dong Cao; Ying Li; Jialin Wang; Haiyang Nan; Youning Wang; Sijia Lu; Qiong Jiang; Xiaoming Li; Danning Shi; Chao Fang; Xiaohui Yuan; Xiaohui Zhao; et al. (Plant Molecular Biology, 2015)

Antibacterial activities of nemonoxacin against clinical isolates of Staphylococcus aureus: an in vitro comparison with three fluoroquinolones - Zhaoxia Li; Youning Liu; Rui Wang; Aimin Li (World Journal of Microbiology and Biotechnology, 2014)

Molecular characterization and expression analysis of lipopolysaccharide and β-1,3-glucan-binding protein (LGBP) from pearl oyster Pinctada fucata - Dianchang Zhang; Jianjun Ma; Jingjing Jiang; Lihua Qiu; Caiyan Zhu; Tianfeng Su; Youning Li; Kaichang Wu; Shigui Jiang (Molecular Biology Reports, 2010)

Salt-induced plasticity of root hair development is caused by ion disequilibrium in Arabidopsis thaliana - Youning Wang; Wensheng Zhang; Kexue Li; Feifei Sun; Chunyu Han; Yukun Wang; Xia Li (Journal of Plant Research, 2008)

Arabidopsis EIN2 modulates stress response through abscisic acid response pathway - Youning Wang; Chuang Liu; Kexue Li; Feifei Sun; Haizhou Hu; Xia Li; Yankun Zhao; Chunyu Han; Wensheng Zhang; Yunfeng Duan; Mengyu Liu; Xia Li (Plant Molecular Biology, 2007)